Daclatasvir + asunaprevir + beclabuvir ± ribavirin for chronic HCV genotype 1‐infected treatment‐naive patients. (6th December 2015) - Everson, Gregory T.; Sims, Karen D.; Thuluvath, Paul J.; Lawitz, Eric; Hassanein, Tarek; Rodriguez‐Torres, Maribel; Desta, Tadesse; Hawkins, Trevor; Levin, James M.; Hinestrosa, Federico; Rustgi, Vinod; Schwartz, Howard; et al.
Abstract: Background and Aims: This phase‐2b study examined the safety and efficacy of an all‐oral, interferon‐free combination of the NS5A replication complex inhibitor daclatasvir (DCV), the NS3 protease inhibitor asunaprevir (ASV), and the nonnucleoside NS5B polymerase inhibitor beclabuvir (BCV) with or without ribavirin in patients with HCV genotype (GT) 1 infection. Methods: A total of 187 patients received 12 weeks of DCV 30 mg BID plus ASV 200 mg BID and BCV 150 mg BID ( n  = 86) or 75 mg BID with ( n  = 21) or without ( n  = 80) weight‐based ribavirin BID. The primary endpoint was HCV RNA <25 IU/ml at post‐treatment week 12 (SVR12). Results: Overall, 90% of patients (169/187) in the combined treatment groups achieved SVR on or after post‐treatment week 12. SVR rates were similar across subgroups (by mITT analysis), i.e. patients with cirrhosis (88%, 14/16), HCV GT‐1a (90%, 137/155), and IL28B non‐CC genotype (90%, 115/128). There were no drug‐related serious AEs or grade 4 AEs. The most frequently reported AEs were headache, diarrhoea, fatigue and nausea. Addition of ribavirin to DCV+ASV+BCV was associated with decreased haemoglobin, compared with DCV+ASV+BCV alone. There were six grade 3/4 laboratory abnormalities noted, all unrelated to the study drugs. Viral breakthrough occurred in 2.5–4.8% of patients across groups and appeared unrelated to BCV dose or ribavirin inclusion. Conclusions: Results support phase 3 evaluation of a twice‐daily, fixed‐dose formulation of this DCV+ASV+BCV regimen with or without ribavirin in HCV GT‐1‐infected patients. Abstract : See Editorial on Page181